Boranka - the largest volunteer reforestation campaign in Europe in terms of the number of volunteers and the number of planted trees - Gotal Dmitrović Lovorka; Čerepinko Darijo; Jozić Nikola (E3S Web of Conferences, 2023)
Public education campaigns and strategically used public relations tactics could enhance broad goals of environmental protection and restoration through building awareness and enticing to action. In case study of Boranka, one of the most successful non-profit ecological campaigns it is presented how by using element of green marketing, smart PR strategies, easy-to-use tools and engaging, emotinal story a number of people could be brought together into collective eco-friendly action. Over the course of four years Boranka resulted in more than 100,000 new trees that have been planted in burned areas throughout Croatia with more than 8,500 volunteers participating in seeding activities while over the HRK 2,170,000 (over the €288,000) was collected in funds and almost HRK 5,000,000 (about €664,000) in material goods, services and advertising space.